D-Optimal design and multi-objective optimization for green extraction conditions developed with ultrasonic probe for oleuropein - Vural, Nilüfer; Algan Cavuldak, Özge; Akay, M. Abdülkadir (Journal of applied research on medicinal and aromatic plants, 2021)
•High added-value compounds and phytochemicals can be obtained by recovery from olive leaves.•A chemometric study, based on soft computing approaches, can be used for a green ultrasound prob extraction process.•Optimization of predicted fuzzy responses can be achieved in multi-objective perspective through NSGA-II.•Soft computing based modelling and optimization tools can be applicable to determine the optimum conditions of the food industry processes. Ultrasonic probe extraction of phenolic compounds from olive leaves was modelled and optimized by using soft computing methods. The effects of amplitude, irradiation time, solvent (MeOH/EtOH) concentration, probe position and duty cycle on total phenolic content (TPC), oleuropein content (OLEc) and total antioxidant activity (TAA) of olive leaf extracts were investigated in multi-objective perspective. The predicted quadratic linear models were obtained by using the least square (LS) approach. They were optimized through the Non-dominated Sorting Genetic Algorithm-II (NSGA-II) and Pareto sets were obtained. A compromise solution was chosen among many non-dominated solutions of experimental conditions by using multi-criteria decision making (MCDM) methods. The fuzzy c-means clustering algorithm (FCM) method was used to select the compromise solution. The optimum conditions of MeOH/H2O ultrasonic probe extraction were determined as; amplitude 81.91 %, irradiation time 14.22 min, MeOH concentration 76.97 %, probe position 3.89 cm, duty cycle 0.93 % and the experimental results obtained under these conditions were 7.19 ± 0.44 mg OLE/g dw, 5.95 ± 0.19 mg/g dw, 88.36 ± 2.47 % for TPC, OLEc and TAA, respectively. For EtOH/H2O ultrasonic probe extraction; the observed results were 5.24 ± 0.08 mg OLE/g dw, 2.22 ± 0.08 mg/g dw, 80.16 ± 1.25 % for TPC, OLEc and TAA, respectively at the optimum conditions of amplitude 79.16 %, irradiation time 12.90 min, EtOH concentration 73.40 %, probe position 1.59 cm, duty cycle 0.97 %.